The Reign and Life of Queen Elizabeth I - Levin, Carole. author. aut Link
XVII, 303 p. 21 illus., 16 illus. in color.
Keywords: This textbook provides an overview of the long reign of Elizabeth I (1558–1603), a highly significant female ruler in a time of great change. It offers an accessible yet detailed survey of the events of her life and reign, followed by thematic chapters exploring key aspects of her time in power and the wider context of politics, culture and society in early modern England. Topics covered range from the composition of the queen's Privy Council; the 'Other' in Elizabethan England; assassination attempts; friendship; entertainment; and dreams. Gathering a great deal of cutting-edge and original research from one of the foremost scholars of Elizabeth's reign, this book is an essential companion for students and a crucial reference work for researchers. .